Pediatric trigger thumb caused by a flexor tendon sheath ganglion. Issue 2 (March 2020) - Murgai, Rajan R.; Lightdale-Miric, Nina
Abstract : Pediatric trigger thumb is a common reason for toddlers to present to a pediatric orthopaedic surgeon. There is controversy over the precise etiology and optimal treatment method. Current accepted diagnostic and treatment algorithms in children have not varied based on etiology. This report describes the clinical presentation and care of a 3-year-old child with pediatric trigger thumb and surgical findings of a large flexor tendon sheath ganglion at the level of the annular pulley with no apparent nodule within the FPL. The potential implications for consideration of etiology in current diagnostic and treatment guidelines are discussed.